SISTEM PAKAR DIAGNOSA PENYAKIT PADA IKAN BUDIDAYA AIR TAWAR DENGAN METODE FORWARD CHAINING - Aristoteles Aristoteles; Wardiyanto Wardiyanto; Ardye Amando Pratama (Universitas Lampung, 2015)
Disease is an unwanted problem in freshwater fish cultivation. Lack of information to prevent the disease and limited number of expert in the field of fishery cause unoptimal harvest that leads to substantial loss. Based on that background, expert system to diagnose disease in freshwater fish cultivation is made in this research. This system is intended to help the fish cultivator in identifying diseases based on the symptoms that the fish have. Therefore, further treatment can be applied to cure the fish. The expert system is web-based with php and MySQL as the programming languages that are used as database. Forward chaining is used as the method of reasoning. This method is used to decide which rule is going to be executed, then it is executed. The process is repeated until the result comes up. This system is able to diagnose 33 diseases in 5 kinds of fish. There are 2 tests in this research which are internal and external. The result of the test shows that the system is able to diagnose well and meet the expectation. Moreover, on the management of the rule, the system is able to run as it is intended. This research has created a web based expert system application that can be used to diagnose diseases based on the facts given and give solutions like an expert.Keywords: Expert System, forward chaining, freshwater fish disease, freshwater fish cultivation.